Modelling the mechanical behaviour of typical wall-to-floor connection systems for cross-laminated timber structures. (1st May 2018) - Izzi, Matteo; Polastri, Andrea; Fragiacomo, Massimo
Highlights: A numerical model that simulates typical wall-to-floor connections is proposed. A method to assess the mechanical properties of nailed joints in CLT is described. Shear and tension tests are reproduced on typical connections for CLT structures. The behaviour under the simultaneous application of shear and tension is analysed. Abstract: This paper proposes a numerical model capable of predicting the mechanical behaviour and the failure mechanism of typical wall-to-floor connections for Cross-Laminated Timber structures. Such systems are assembled with angle brackets and hold-downs, anchored to the wall and floor panels with profiled nails and bolts. The metal connector and the elements to which it is fastened are modelled using 3D solid bodies, while the steel-to-timber joints are simulated as non-linear hysteretic springs. Shear and tension tests are reproduced on two connection systems and results are compared to the test data obtained from similar configurations. Simulations lead to accurate predictions of the mechanical behaviour (i.e. elastic stiffness, maximum load-carrying capacity, and shape of the hysteresis cycles) and energy dissipation. Finally, the performance when lateral and axial loads are applied simultaneously is investigated. Analyses are carried out by varying the inclination of the load, with respect to the axis of the connector, between 0° and 90°. Results exhibit a quadratic interaction relationship between shear and tension loads, and prove that their coupled effect influences the stiffness and the maximum load-carrying capacity.